Learning about Professionalism within Practice-based Education: What are we looking for? - Mason, Rosemarie; Butterfint, Zoe; Allen, Rachel; Bygrave, Katherine; Gelder, Emily; Pomroy, Emma (International Journal of Practice-based Learning in Health and Social Care, 2015)
Health and social care professions are being held to account concerning their professionalism in ways that would have been unprecedented in the recent past. Students of the School of Health Sciences (HSC) within the University of East Anglia (UEA) in the United Kingdom have professionalism taught and assessed in a number of ways and have overt opportunities to develop their professional performance during practice education. In order to augment this further, a UEA Professionalism Charter has been developed, which helps students to define, learn and apply professionalism in a particular way. Since professionalism is being scrutinised by a number of bodies it is important that there is agreement about its nature. Without an overt definition of professionalism from the Health and Care Professions Council (the regulatory body for occupational therapy, physiotherapy and speech and language therapy) this study set out to explore what could be learned about this body’s perspective through analysis of its Fitness to Practice hearings. The outcome revealed that a definition could be identified and that this bears a close resemblance to that used within the UEA Professionalism Charter. The study therefore supports the continued use of the Charter